One-stage vs. two-stage thoracoscopic surgery for synchronous bilateral pulmonary nodules: a systematic review and meta-analysis - Eduardo Noleto da Nobrega Oliveira, Rachid; Franceschini Machado, Guilherme; Cabianca Moriguchi Caetano Salvador, Isabella; Duarte D´Ambrosio, Paula; Delgado, Lucas Monteiro; Passos, Felipe S.; Caldonazo, Tulio (Frontiers in Surgery, 2026)
IntroductionThe optimal surgical strategy for synchronous bilateral pulmonary nodules remains unclear. One-stage bilateral resections may offer logistical and clinical advantages, but safety concerns persist regarding bilateral complications.MethodsWe conducted a systematic review and meta-analysis of studies comparing one-stage vs. two-stage pulmonary resections in adult patients with synchronous bilateral nodules. Ten observational studies were included, encompassing 1,015 patients. Continuous outcomes were assessed using mean differences (MDs) and binary outcomes with odds ratios (ORs), applying DerSimonian and Laird random-effects models. Subgroup and meta-regression analyses were performed. Statistical analyses were conducted using R software (v4.4.1).ResultsOne-stage resection was associated with significantly reduced operative time (MD −24.36 min; 95% CI −40.59 to −8.13), shorter hospital stay (MD −2.79 days; 95% CI −4.25 to −1.33), and lower direct surgical costs (MD −5,543.73 USD; 95% CI −6,601.05 to −4,486.40). No significant differences were observed in intraoperative blood loss, persistent air leak, or arrhythmia. Subgroup analysis revealed that the type of pulmonary lesion influenced hospital stay, while meta-regression showed no effect of lobectomy rate.ConclusionsOne-stage bilateral resection demonstrates greater efficiency without increased morbidity, supporting its use in experienced centers. These findings suggest that a single-anesthetic approach may facilitate earlier recovery and timely systemic therapy in selected patients.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251048804, identifier: CRD420251048804.